(untitled) (Research, Society and Development, 2022)
The population of animals in Brazil has been growing significantly over the years and in an attempt to control female dogs, many owners use contraceptives indiscriminately. Thus, the present work focuses on the analysis and discussion of the objective and epidemiological aspects of the population in the use of contraceptive drugs in decades. There were a total of 18 medication forms corresponding to the use or not of income, encompassing the personal profile of each population, as well as age, gender, family and education, knowledge about the consequences of this animal and about the indication of this conduct to other people. The main findings elaborated that were affirmed to higher education in 89.3% of the administration of contraceptives were never made of its administration, concomitantly with the findings of prevalence of incomplete (64.07%) ) minimum income and complete monthly income (20.95 %) and family members of up to 1 salary (35%) and income of 1 to 3 higher monthly payments (35%). To conclude that the decision to use medication can be evaluated through stimuli from external and intrinsic factors, such as financial, educational, ease of delivery, age and gender.